Structuring The Relocation Of The Central Market By The Trade And Industry Agency Of Gorontalo City - Siti Maria Ulfa (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The purpose of this research is to determine the Central Market Relocation Arrangement by the Gorontalo City Trade and Industry Service. The research method used is a qualitative method, a research approach regarding the Central Market Relocation Arrangement by the Gorontalo City Trade and Industry Service. The qualitative approach emphasizes natural phenomena or symptoms that occur in a fundamental and naturalistic manner, and is carried out in the field, not in the laboratory. This approach is often referred to as naturalistic inquiry or field study. According to Lofland, the primary data used in qualitative research are keywords and phrases. The summary of the data above can come from documents, reports, or observation results. Based on the research results, analysis of the discussion of this research concludes that the Central Market Relocation Arrangement by the Gorontalo City Trade and Industry Service, seen from the aspects of infrastructure development, officer capability, communication, has not been implemented optimally, based on the results of interviews that have been described with several informants, it has not been optimally implemented by Gorontalo City Department of Trade and Industry, so that the arrangement of the Central market is not yet optimal because infrastructure development which should focus on main supporting facilities is not carried out. From the description of the results of interviews with informants, the ability of officers to provide guidance for controlling traders and buyers which can support the arrangement of the Gorontalo City Central Market area has not been optimal. Based on the description of the results of interviews with the informants involved, it can be concluded that the Relocation Arrangement for the Central Market of Gorontalo City is not optimal when viewed from the perspective of the communication that has been established between the Department of Trade and Industry of Gorontalo City and the Limbau U II sub-district, this communication is not optimal, as can be seen from the changes Market conditions still have the same problems, especially regarding controlling traders and buyers.